2005
DOI: 10.3989/cyv.2005.v44.i5.350
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades mecánicas de aerogeles híbridos de sílice

Abstract: Se han obtenido aerogeles híbridos de sílice orgánico-inorgánico por aplicación de ultrasonidos de alta potencia en los precursores líquidos y posterior secado del gel húmedo en condiciones supercríticas en etanol. Las cadenas orgánicas no se degradan térmicamente y aceleran el proceso de contracción de la red por activación térmica. Los ultrasonidos inducen un entrecruzamiento de cadenas orgánicas que unen los cúmulos de sílice porosa y evitan su ciclidación. Los ensayos de ruptura en compresión uniaxial indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…But a large increase of the maximum strain (more than 4-fold) was achieved in sample TD1.25. All these changes are in accordance with the general behaviour previously reported for similar samples [11,12,[35][36][37]. Therefore, the incorporation of the Table 3 Mechanical properties of the dry samples and wet samples after saturation by the absorption of two different liquids, motor oil and liquid PDMS.…”
Section: Structure Of the Wet Samplessupporting
confidence: 89%
“…But a large increase of the maximum strain (more than 4-fold) was achieved in sample TD1.25. All these changes are in accordance with the general behaviour previously reported for similar samples [11,12,[35][36][37]. Therefore, the incorporation of the Table 3 Mechanical properties of the dry samples and wet samples after saturation by the absorption of two different liquids, motor oil and liquid PDMS.…”
Section: Structure Of the Wet Samplessupporting
confidence: 89%
“…They found that addition of organic components changes the behavior of the material from a brittle solid to a rubber elastomer; a result that was also found by Piñero et al [21] who studied the compressive properties of aerogels produced using the same precursors. From experimental results presented in [20], it is clear that the Young's modulus of the hybrid aerogels is reduced when the amount of organic material added is increased.…”
Section: Structure Of Ch 3 -Added Silica Aerogels and Xerogelssupporting
confidence: 62%
“…The changes of the mechanical properties of hybrid aerogels are due to the reorganization of the internal structure of the material when the amount of organic material is increased. If the structure has a small organic content, the mechanical response is dominated by the brittle inorganic structure, but when the amount of organic material surpasses a certain level an organic matrix is formed and the material becomes rubbery [20,21].…”
Section: Structure Of Ch 3 -Added Silica Aerogels and Xerogelsmentioning
confidence: 99%
See 2 more Smart Citations